The collected poems of Howard Nemerov. - Nemerov, Howard (Chicago : University of Chicago Press, 1981)
Presents the poems of twentieth-century American writer Howard Nemerov that were previously published in collections spanning 1947-75.
Includes index.
Adult
Keywords: American poetry